Nano-LC–MS/MS for the quantitation of ceramides in mice cerebrospinal fluid using minimal sample volume - Thomas, D.; Eberle, M.; Schiffmann, S.; Zhang, D.D.; Geisslinger, G.; Ferreirós, N. (Talanta (Oxford), 2013)
A new nano-liquid chromatography–ESI–MS/MS method has been developed for the sensitive quantitation of C8:0, C16:0, C18:0, C18:1, C20:0, C24:1 and C24:0 ceramide in cerebrospinal fluid of mice using minimal sample volume. Volumes of 2µL CSF were undertaken a simple, fast extraction procedure involving protein precipitation with methanol and dilution. Ceramides were separated by nano-liquid chromatography with a reversed phase C8 column and detected with a triple quadrupole mass spectrometer. C17:0 ceramide was used as internal standard. The method has been validated in terms of linearity, lower limit of quantitation, precision, accuracy and autosampler stability. Calibration curves covered a range of 2.25–120pg/µL for most ceramides (7.5–120pg/µL for C24:0 ceramide). The lower limits of quantitation determined for C8:0, C16:0, C18:1, C18:0, C20:0 and C24:1 ceramide were 0.225pg on column (2.25pg/µL) and that for C24:0 ceramide 0.750pg on column (7.5pg/µL). Intra- and interday precision and accuracy values, expressed as relative standard deviation and relative error, respectively, were lower than 15% in all cases. Autosampler stability for calibration standards and CSF samples was proven for at least 24h for all analytes. The suitability of the method has been demonstrated by quantifying the analytes, except the non-endogenous C8:0 ceramide, in cerebrospinal fluid samples of 12 mice. Calculated concentrations ranged from 3 to 120pg/µL in cerebrospinal fluid for all analytes, except for C24:0 ceramide, which could not be detected in any of the analyzed samples. •A very high sensitive method for ceramides in cerebrospinal fluid was developed.•Only 2µL sample volume was required.•Validation according to the FDA guidelines was performed.•First approach using nano-LC–MS/MS for quantitation of ceramides.